Human being, environmental protection and conservation of biodiversity: the international environmental law perspective / M. Sabri Yusof - Yusof, M. Sabri (2002)
This paper will bring into view the impact of environmental and biodiversity depletion on human being and their very existence; and the role of international environmental law in balancing the human needs and issues regarding environmental protection and conservation of biodiversity.